2019
DOI: 10.1177/1352458519861270
|View full text |Cite
|
Sign up to set email alerts
|

Change in multiple sclerosis prevalence over time in Australia 2010–2017 utilising disease-modifying therapy prescription data

Abstract: Objective: Determine the prevalence of multiple sclerosis (MS) in Australia in 2017 using MS-specific disease-modifying therapy (DMT) prescription data and estimate the change in prevalence from 2010. Methods: DMT prescriptions were extracted from Australia’s Pharmaceutical Benefits Scheme (PBS) data for January–December 2017. Percentages of people with MS using DMTs (DMT penetrance) were calculated using data from the Australian MS Longitudinal Study. Prevalence was estimated by dividing the total number of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 23 publications
2
32
1
Order By: Relevance
“…The United States validated a case-ascertainment algorithm and reported an almost doubling of prevalent cases to 913,925 in 2019. 5 An increasing prevalence of MS has also been reported across the Middle East and North African region, 6 in the Russian Federation, 7 Canada, 8 Australia 9 and in several European countries (Denmark, Germany, Poland, the United Kingdom). The Global Burden of Disease (GBD) 2016 Multiple Sclerosis Collaborators similarly reported that the prevalence of MS had risen between 1990 and 2016, estimating that there were 2,221,188 (95% Uncertainty Interval 2,033,866–2,436,858) persons living with MS in 2016.…”
Section: Resultsmentioning
confidence: 99%
“…The United States validated a case-ascertainment algorithm and reported an almost doubling of prevalent cases to 913,925 in 2019. 5 An increasing prevalence of MS has also been reported across the Middle East and North African region, 6 in the Russian Federation, 7 Canada, 8 Australia 9 and in several European countries (Denmark, Germany, Poland, the United Kingdom). The Global Burden of Disease (GBD) 2016 Multiple Sclerosis Collaborators similarly reported that the prevalence of MS had risen between 1990 and 2016, estimating that there were 2,221,188 (95% Uncertainty Interval 2,033,866–2,436,858) persons living with MS in 2016.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, given we did not have individual level data of the 2014-15 NHS, we were not able to exclude PwMS in the 2014-15 NHS. However, it would have only included approximately 20 people with MS out of the 19,259 NHS participants, based on 2017 MS prevalence estimates [50].…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence to suggest that the prevalence of multiple sclerosis in Victoria is increasing and that there is a high incidence of inflammatory bowel disease in Geelong, Victoria, among the highest reported in the international literature . Therefore, it is also plausible that vitamin D or another environmental factor is playing a role in the rates of other autoimmune diseases in Victoria.…”
Section: Discussionmentioning
confidence: 99%